2008
DOI: 10.1080/13693780802172017
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral phaeohyphomycosis caused byScytalidium dimidiatum: a case report from India

Abstract: We report a case of cerebral phaeohyphomycosis caused by Scytalidium dimidiatum (synanamorph Nattrassia mangiferae) in a young, apparently immunocompetent Indian male. Etiological diagnosis was made by recovery of the fungus in culture and histopathological examination. The infection proved fatal despite aggressive antifungal therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 19 publications
(15 reference statements)
1
17
0
2
Order By: Relevance
“…Cases of mycetoma, subcutaneous and cerebral infections, fungaemia and other deep-seated pathologies have been reported less frequently, mainly affecting patients with predisposing factors such as diabetes mellitus, solid organ transplant, corticosteroid therapy, systemic lupus erythematosus and trauma [2][3][4][5][6][7][8][9]. Optimal therapy has not been developed for diseases caused by N. dimidiatum and several cases of fatal invasive infections have been reported despite antifungal therapy [4,5,8].…”
Section: Introductionmentioning
confidence: 99%
“…Cases of mycetoma, subcutaneous and cerebral infections, fungaemia and other deep-seated pathologies have been reported less frequently, mainly affecting patients with predisposing factors such as diabetes mellitus, solid organ transplant, corticosteroid therapy, systemic lupus erythematosus and trauma [2][3][4][5][6][7][8][9]. Optimal therapy has not been developed for diseases caused by N. dimidiatum and several cases of fatal invasive infections have been reported despite antifungal therapy [4,5,8].…”
Section: Introductionmentioning
confidence: 99%
“…Mortality was Ͼ70%. Since that review in 2004, over 50 cases have been reported, with C. bantiana remaining the most frequently seen isolate (131,4,17,16,22,31,40,70,78,93,121,139,170,189,243,244,268,272,276,328,332,341,363,380,399,420,433,448,450,467,476,545,575,636,657,696,700,721,731,733,754,759). A new species, Fonsecaea monophora, has been reported since that time and appears to have a predilection for causing CNS disease, in contrast to its related species, F. pedrosoi (420,721,733).…”
Section: Phaeohyphomycosismentioning
confidence: 99%
“…This organism is a plant pathogen, and the name should not be used for human isolates. N. dimidiatum primarily produces infections mimicking those caused by dermatophytes on skin and nails (218,459), although there are occasional reports of ocular infections (26) and deep mycoses in immunocompromised individuals (73,476,694,801).…”
Section: Pleosporalesmentioning
confidence: 99%
“…The dematiaceus variety is responsible not only for superficial infection as N. dimidiatum var. hyalinum, but also for invasive and deeper infection such as subcutaneous infections [20][21], sinusitis [22][23], endophtalmitis [24], cerebral pheohyphomycosis [25], pneumonia [8,26], and disseminated infections [27][28][29]. As the number of mycoses caused by both varieties is increasing [7,9,30] there is a renewed interest in the study of these fungi.…”
Section: Dimidiatum Was Isolated From Environmental Samples and Patiementioning
confidence: 99%